Implementation of Evidence-Based Practice Precepts in Psychotherapy and Recommendations for Research and Practice - Middleton, Jerry C.; Azzi, Michelle; Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2022)
This brief report addresses the attitudes of psychotherapy providers and North American psychology regulatory leaders toward evidence-based practice (EBP) precepts as applied to their psychotherapy practices. Secondary descriptive analyses of a two-phase survey concerning these attitudes of Canadian psychotherapy providers (n = 684) and psychology regulatory leaders (n = 32) were undertaken to inform the perceived utility and implementation of EBP precepts within psychotherapy practices. Results indicated that while there is general agreement among attitudes toward EBP precepts as applied to the routine clinical practices of psychotherapy providers and leaders, they are nuanced depending on the EBP tenet in question. Results are situated within the extant empirical literature on the EBP of psychotherapy in particular and of psychology more broadly, with recommendations for future research provided. While the zeitgeist is alive and well for the uptake of EBP in psychotherapy practice, important challenges remain for its advancement and implementation.